Photoluminescent and gas-sensing properties of ZnO nanowires prepared by an ionic liquid assisted vapor transfer approach - Kittitat Subannajui (2018)
In this work, the ionic liquid assisted technique was used to control the growth characteristic of ZnO nanowires (NWs). The major change after adding ionic liquid into the growth system was the change in NW growth orientation, which was shifted from polar c- to non-polar a-orientation. Room temperature photoluminescence demonstrates a big reduction of the green luminescence which implies an annihilation of deep level emission. We propose two possible mechanisms responsible for the reduction of the green emission: The first mechanism is the passivation of ZnO NWs surface by fractions of ionic liquid employed for the growth, which further reduces the green emission. The second mechanism is the reduction of the defect density by changing the growth orientation. By using a semi-empirical Austin Model 1 method, the formation energy of oxygen vacancies in c- and a-oriented ZnO NWs has been simulated and compared. Accordingly, the gas-sensor constructed from ionic liquid assisted ZnO nanowires does not response when exposed to CO. This inert sensitivity is caused by the suppressed adsorption of CO molecules due to the presence of the passivation layer. The study presented here provides a new insight of how the recombination appears at the surface of ZnO NWs. © 2012 American Institute of Physics.